Designing Specific HSP70 Substrate Binding Domain Inhibitor for Perturbing Protein Folding Pathways to Inhibit Cancer Mechanism - Coşkun, Kübra A.; Koca, İrfan and Gümüş, Mehmet and Tutar, Yusuf (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: HSP70 is a survival factor for tumor cells in transformation and in tumor progression as well as in anti-apoptotic response. Objective: Several inhibitors targeting HSP70 ATPase function displayed off-target effects, but PES, which targets the HSP70 substrate binding domain, prevents tumor cell survival prominently. However, PES may not bind HSP70 in the absence of nucleotide. This research aimed to design a unique inhibitor molecule that works both in the presence and absence of nucleotides to amplify inhibition. Methods: A set of chimeric coumarine-pyrazole derivatives were determined by in silico techniques and synthesized to elucidate their inhibitory effects. Cell viability experiments displayed KBR1307 as the most efficient inhibitor. A set of characterization experiments were performed, and the results were compared to that of PES agent. Binding constant, ATP hydrolysis rate, and percent aggregation were determined in the presence and absence of inhibitors. Results: In silico docking experiments showed that only KBR1307 binds the HSP70 substrate binding domain and interacts with cochaperone interface. Binding experiments indicated that KBR1307 binds HSP70 both in the presence and absence of nucleotides, but PES does not. Both inhibitors significantly lower HSP70 ATPase activity and substrate protein disaggregation activity. However, KBR1307 displays a lower IC50 value at the MCF-7 cell line compared to PES. Both inhibitors do not alter HSP70 secondary structure composition and overall stability. Conclusion: KBR1307 effectively inhibits HSP70 compared to PES and provides a promising template for novel anticancer drug development.
Keywords: substrate binding domain